Diseño de un Algoritmo mediante procesamiento de imágenes para la determinación y control de la posición del brazo Amatrol Pegasus I en el Instituto Tecnológico de Costa Rica Sede San Carlos - Durán-Solano, Randald (Instituto Tecnológico de Costa Rica, 2018)
The document presents the proposal of design, evaluation and implementation of an algorithm that allows to give mobility to an industrial gear. The project was raised by the School of Electronics Engineering at the regional headquarters of San Carlos, with the aim of reactivating the use of the Amatrol's Pegasus I industrial arm that is in the digital systems laboratory. The project was proposed for the elaboration of an algorithm that through image processing allows to determine the position of the equipment and the angles of inclination of its extremities to be able to generate a feedback control of the motors. The project was worked on three main modules, the process of detection, tracking and processing of the images, the communication system for information transfer and the algorithm of processing and activation of the microcontroller motors. The objective of this report is to show how the algorithm and the research process carried out were developed, for the implementation was made the analysis of different solution alternatives corresponding to the hardware and software, different execution tests were carried out and the analysis of the factors to consider in the development of an algorithm implementing computer vision. The work processes were developed for each independent vision input, and the software design for the activation of the respective control signals of the DC motors required for the positioning.
Proyecto de Graduación ( Licenciatura en Ingeniería Electrónica). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Electrónica, 2018.
Keywords: Equipo industrial; Hardware; Software; Microcontroladores; Computadoras; Lenguaje de programación; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics